2019
DOI: 10.1155/2019/6592927
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Ventricular Arrhythmia and the Role of Overdrive Pacing in the Suppression of the Electrical Storm

Abstract: Ventricular arrhythmia storm is a state of cardiac instability characterized by multiple ventricular arrhythmias or multiple ICD therapies within a 24-hour duration. Management of this life-threatening state depends on the reversal of the cause besides either electrical or medical management of the arrhythmia. We report a case of a 54-year-old male who underwent a percutaneous coronary intervention following massive acute myocardial infarction. Afterwards, he developed frequent life-threatening ventricular arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To our knowledge, temporary use of VOP has been previously described by Magdi et al in a patient that underwent PCI and had a large anterolateral AMI for the purpose of control of the resistant arrhythmia [ 11 ]. Similarly, although a different case was described by Kurisu and colleagues, in this case report, ES occurred seven days after acute anterior myocardial infarction and stent implantation and it was also complicated with ventricular fibrillation that occurred due to subacute stent occlusion, thus requiring emergent balloon angioplasty [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, temporary use of VOP has been previously described by Magdi et al in a patient that underwent PCI and had a large anterolateral AMI for the purpose of control of the resistant arrhythmia [ 11 ]. Similarly, although a different case was described by Kurisu and colleagues, in this case report, ES occurred seven days after acute anterior myocardial infarction and stent implantation and it was also complicated with ventricular fibrillation that occurred due to subacute stent occlusion, thus requiring emergent balloon angioplasty [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 236 , 237 Temporary overdrive atrial or ventricular pacing in patients without ICD demonstrated its efficiency in preventing recurrence of drug-resistant VA in several case reports, mainly in the context of acute or recent myocardial ischaemia. 238 , 239 Moreover, bradycardia pacing might be useful in some patients with brady-mediated PVT.…”
Section: Acute Managementmentioning
confidence: 99%